Advanced Poly‐Fiber Hybrid‐Nanocomposites: Fabrication and Strengthening With Silicon Carbide Integration - Solairaju Jothi Arunachalam; Rathinasamy Saravanan; T. Sathish; Rebwar Nasir Dara; Mustafa Abdullah; Eman Ramadan Elsharkawy; Ankur Bahl; A. Johnson Santhosh (Engineering Reports)
ABSTRACT This study examines the mechanical and thermal properties of materials made from jute, glass, and kenaf fibers reinforced with various weight percentages of silicon carbide (SiC). The composites were manufactured with different SiC loadings, and their tensile strength, flexural strength, fracture toughness, moisture absorption, and thermal stability were evaluated. Tensile and flexural examinations were conducted to assess the structural integrity of the laminate under stress, revealing that the incorporation of 3% SiC led to a 27% improvement in tensile strength and an 18% increase in flexural strength, indicating enhanced load‐bearing capacity and flexibility. Microhardness and fracture toughness were also measured to determine resistance to crack propagation; results showed a 28% rise in microhardness and a 33% enhancement in fracture toughness with 3% SiC, signifying improved durability for structural applications. A moisture absorption study was carried out to evaluate the hydrophobic properties of the composites, which are crucial for long‐term performance in humid environments. The analysis demonstrated a significant reduction in water uptake with 3 wt% SiC, improving the composite's performance by minimizing water‐induced degradation. Thermogravimetric analysis (TGA) was employed to assess thermal stability and decomposition behavior, with findings indicating improved thermal stability with increasing SiC percentage. Overall, the integration of 3% SiC significantly enhanced mechanical strength, crack resistance, and moisture resistance, making the composite more suitable for demanding structural and environmental conditions.